1991
DOI: 10.1055/s-2007-1025439
|View full text |Cite
|
Sign up to set email alerts
|

Langzeituntersuchung zur anthracyclininduzierten Kardiomyopathie bei Kindern und Jugendlichen

Abstract: In order to detect changes in cardiac function, electrocardiographic, echocardiographic and radiologic studies were performed in 71 patients (age 1-26 yrs) who had been treated at the University Children's Hospital Berlin because of malignant diseases according to protocols of the DAL/GPO and had received anthracyclines (doxorubicin or daunorubicin) at cumulative doses up to 480 mg/m2 (median 280 mg/m2). Clinically overt cardiomyopathy was observed in one girl and required transient administration of digoxin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
2
4
0
Order By: Relevance
“…While some studies support the ®ndings of Lipshultz et al [20] and Steinherz et al [28] [e.g. 1,9], others arrive at much lower rates of subnormal measurements [11,17,19,25]. In the present study, in which only relatively low ADR doses are encountered, only one patient has a reduced shortening fraction.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…While some studies support the ®ndings of Lipshultz et al [20] and Steinherz et al [28] [e.g. 1,9], others arrive at much lower rates of subnormal measurements [11,17,19,25]. In the present study, in which only relatively low ADR doses are encountered, only one patient has a reduced shortening fraction.…”
Section: Discussionsupporting
confidence: 78%
“…Several recent studies have documented high rates of cardiac dysfunction in long-term survivors of paediatric malignancies treated with anthracyclines [1,9,17,19,20,27,28]. Lipshultz et al [20], for example, found abnormal contractility and/or afterload in 57% of 110 ALL patients 1±15 years after treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whether these alterations are reversible after therapy, as reported for the shortening fraction [13], is unknown. Longterm studies are needed to answer the predictive value of these findings.…”
Section: Discussionmentioning
confidence: 94%
“…Early diagnosis of anthracycline-induced Cardiotoxicity below a maximum dose is desirable, because the appearance of side-effects is not always correlated with the cumulative dose [5,13]. Even when the anthracycline dose is limited to less than 450 mg/m 2 cardiomyopathy must be expected in 4% of treated patients [5].…”
Section: Discussionmentioning
confidence: 98%